“Misogyny is Rampant:” Harassment, Bullying, and Their Impact on Professional Satisfaction among Female Legal Practitioners in California - Becker, Patricia (Women & criminal justice, 2024)
The purpose of this study is to examine gender differences in harassment and bullying and their effect on professional satisfaction in a sample of legal practitioners in California (n = 486). Quantitative data indicate that harassment and bullying significantly decrease the odds of professional satisfaction. As compared to men, women experienced greater professional dissatisfaction, and in particular, harassment and bullying had a greater negative impact on their professional satisfaction. Qualitative data provide a deeper understanding of the respondents’ experiences. Policy implications derived from this research to address workplace harassment and bullying at the macro and micro levels are discussed.